(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
The article deals with the problems of formation and development of a true system of local self-government in Kazakhstan, since, as the President of the Republic of Kazakhstan K.Zh. Tokayev noted, it is necessary to “implement a real decentralization of local self-government”. The Constitution of the Republic of Kazakhstan prescribes norms regulating the activities of local self-government bodies, but in practice these constitutional norms have not been implemented. The Head of State noted that “there was an imitation, not local self-government.” President of the Republic of Kazakhstan Tokayev K.Zh. emphasized that “today local self-government bodies have a hybrid nature, being at the same time an institution of local public administration and local self-government. Therefore, it is necessary to clearly define the powers of both maslikhats and akimats on a legislative basis. It is necessary to clearly define their functions and powers and provide them with everything necessary - material and technical base and sufficient financial resources.